Neuropsychological alterations after coronary artery bypass graft surgery - Sirilak Suksompong (2018)
Objective: To evaluate neuropsychological dysfunction in patients following elective coronary artery bypass graft surgery at Siriraj Hospital. Patients and Method: One hundred and ten patients who were scheduled for elective coronary artery bypass graft surgery were included in this study. We used the Thai Mental State Examination (TMSE) in order to detect the presence of cognitive impairment after coronary artery bypass graft surgery. The examinations were conducted on two consecutive occasions; first preoperatively, the day before surgery, secondly on the third - fifth postoperative day. The patients' clinical characteristics were assessed perioperatively. Results: The overall occurrence of neuropsychological deficit was 18.18 per cent. Predictors of neuropsychological dysfunction were older age and preexisting disease such as hypertension, hypercholesterolemia and renal insufficiency. Other risk factors such as gender, history of congestive heart failure, myocardial infarction, diabetes mellitus, dysrhythmia, cardiopulmonary bypass time, hemoglobin during cardiopulmonary bypass <7 g/dl, hemoglobin on admission to surgical cardiac care unit <10 g/dl, and atrial fibrillation arising after surgery were not significant. Conclusion: Neuropsychological impairments after coronary artery bypass graft surgery are relatively common. This study did not find an increased incidence with respect to gender as other studies have done. However, long-term follow-up of these patients would be very valuable.